A five‐year follow‐up of untreated patients with chronic lymphocytic leukaemia treated with ofatumumab and chlorambucil: final analysis of the Complement 1 phase 3 trial. (31st March 2020) - Offner, Fritz; Robak, Tadeusz; Janssens, Ann; Govind Babu, K.; Kloczko, Janusz; Grosicki, Sebastian; Mayer, Jiri; Panagiotidis, Panagiotis; Schuh, Anna; Pettitt, Andrew; Montillo, Marco; Werner, Olena; et al.
Abstract: The Complement 1 trial investigated the efficacy and safety of ofatumumab + chlorambucil with chlorambucil monotherapy in patients with previously untreated chronic lymphocytic leukaemia (CLL). On long‐term follow‐up in the chemoimmunotherapy arm vs. the chemotherapy arm there was an estimated 12% (not significant) and 39% risk reduction in overall survival and progression‐free survival, respectively. A high rate (61%) of treatment with next‐line therapies in both the treatment arms may dilute any potential OS difference and confound the interpretation of the OS results. Addition of ofatumumab to chlorambucil demonstrated clinical benefit and tolerability as a frontline treatment option in patients unfit for fludarabine‐containing therapy, with no new safety concerns.